A Dual-Targeted Soybean Protein Is Involved in Bradyrhizobium japonicum Infection of Soybean Root Hair and Cortical Cells - Marc Libault; Manjula Govindarajulu; R. Howard Berg; Yee Tsuey Ong; Kari Puricelli; Christopher G. Taylor; Dong Xu; Gary Stacey (Molecular Plant-Microbe Interactions, 2011)
The symbiotic interaction between legumes and soil bacteria (e.g., soybean [Glycine max L.] and Bradyrhizobium japonicum]) leads to the development of a new root organ, the nodule, where bacteria differentiate into bacteroids that fix atmospheric nitrogen for assimilation by the plant host. In exchange, the host plant provides a steady carbon supply to the bacteroids. This carbon can be stored within the bacteroids in the form of poly-3-hydroxybutyrate granules. The formation of this symbiosis requires communication between both partners to regulate the balance between nitrogen fixation and carbon utilization. In the present study, we describe the soybean gene GmNMNa that is specifically expressed during the infection of soybean cells by B. japonicum. GmNMNa encodes a protein of unknown function. The GmNMNa protein was localized to the nucleolus and also to the mitochondria. Silencing of GmNMNa expression resulted in reduced nodulation, a reduction in the number of bacteroids per infected cell in the nodule, and a clear reduction in the accumulation of poly-3-hydroxybutyrate in the bacteroids. Our results highlight the role of the soybean GmNMNa gene in regulating symbiotic bacterial infection, potentially through the regulation of the accumulation of carbon reserves.